Effect of the cognitive rehabilitation in patients with mild cognitive impairment and identified brain atrophy - Petr Nilius; Petra Krulová; Dagmar Beránková; Pavel Ressner; Olga Zapletalová; Jana Minarčíková; Jan Pouchlý (University of Ostrava, 2015)
Aim: The main objective of this study was to analyse the development of cognitive functions and effect of cognitive rehabilitation on patients diagnosed with mild cognitive impairment (MCI), as a result of brain atrophy. Design: A quantitative non-randomized intervention study on a control sample of patients. Methods: The effect was observed in a group of patients ranging 59-91 years of age (N = 36). Only patients fulfilling the diagnostic criteria of mild cognitive disorder diagnosed by tomography (CT) that had undergone 22 sessions, were involved in the clinical sample (n = 21). The control sample (n = 15) consisted of patients without any neurological diagnosis and who did not undergo cognitive sessions. Results: The effect of cognitive rehabilitation was measured by Addenbrooke's cognitive test, revised in 2010 (ACE-R); affective changes were measured by Beck´s scale of depression BDI-2 and by a scale used to detect anxiety and depression: the Hospital Anxiety and Depression Scale (HADS). Subjective change and improvement were observed using the Clinical Global Impression (CGI) psychiatric scale. Changes in the functional state of patients were measured by means of the activities of daily living scale (ADL), including the instrumental version (IADL). The effect was examined in the form of entry and output tests, which were verified by statistical analysis, a significant level being p > 0.05. Conclusions: Significant differences in verbal tests and ACE-R were observed in the clinical sample of patients. Some significant changes were observed in the field of affective symptoms, according to the HADS and BDI-2. The clinical sample showed a significant improvement in subjective clinical state (CGI). The ADL and IADL questionnaires seem to have been inadequate for purpose due to their low sensitivity. The effect of cognitive rehabilitation in patients diagnosed with mild cognitive disorder can be seen and verified in comparison with the control sample, which did not suffer from any neurological disorder and did not undergo cognitive sessions. Cognitive rehabilitation may serve as a useful tool for improving cognitive activation in patients diagnosed with brain atrophy. Results are in line with the current state of knowledge and have an overlap in nursing care.